ЗНАЧЕНИЕ ОВЕЦ В ПОДДЕРЖАНИИ СИНАНТРОПНЫХ ОЧАГОВ ТЕНИИДОЗОВ НА ЮГЕ КАЗАХСТАНА (Experimental biology, 2009)
There was studied the ecological base of spreading оf farm animals’ echinococcosis in the southern Kazakhstan recording the transformation of agriculture technologies in conditions of transition economics. There was established the biotic potention of taeniid were supported by sinanthropic sources. The high density of population of domestic animals and its pressing to the common pastures were leading to infection of wild animals by metacestodes
Keywords: ecological base; farm animals’ echinococcosis